Diode laser using narrow bandwidth interference filter at 852 nm and its application in Faraday anomalous dispersion optical filter - 蒋招杰 周琦 陶智明 张晓刚 张盛楠 祝传文 林平卫 陈景标 (Chinese physics B, 2016)
We demonstrate an 852-nm external cavity diode laser（ECDL） system whose wavelength is mainly determined by an interference filter instead of other wavelength selective elements. The Lorentzian linewidth measured by the heterodyne beating between two identical lasers is 28.3 k Hz. Moreover, we test the application of the ECDL in the Faraday atomic filter.Besides saturated absorption spectrum, the transmission spectrum of the Faraday atomic filter at 852 nm is measured by using the ECDL. This interference filter ECDL method can also be extended to other wavelengths and widen the application range of diode laser.